2021
DOI: 10.1186/s12876-021-01672-1
|View full text |Cite
|
Sign up to set email alerts
|

Routine colonoscopy may be needed for uncomplicated acute right colonic diverticulitis

Abstract: Background Routine colonoscopy is recommended to determine the coexistence of colon cancer after medical treatment for colon diverticulitis. However, in the case of uncomplicated diverticulitis diagnosed by computed tomography, the clinical relevance of routine follow-up colonoscopy has recently been debated. Yet, the role of follow-up colonoscopy for right colon diverticulitis, which tends to develop at a younger age than left colon diverticulitis, has not been specifically evaluated. Therefor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…The possible disadvantages of this approach are the difficulty in dissecting the inflamed diverticulum and the risk of inadequate treatment, as there is a risk of advanced adenomas and neoplasia. 22 30 Although none of our patients had incidental findings of cancer on the anatomopathological examination, other authors 25 30 have reported them.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The possible disadvantages of this approach are the difficulty in dissecting the inflamed diverticulum and the risk of inadequate treatment, as there is a risk of advanced adenomas and neoplasia. 22 30 Although none of our patients had incidental findings of cancer on the anatomopathological examination, other authors 25 30 have reported them.…”
Section: Discussionmentioning
confidence: 70%
“…22 Lee et al evaluated 330 patients with uncomplicated RCD and revealed that 20.9% had adenomas detected on follow-up colonoscopy, suggesting that routine colonoscopy should be advised even for patients with an uncomplicated crisis. 30 Regarding the classification of acute diverticulitis, in 1978, Hinchey et al 31 proposed classifying perforated diverticulitis from stages I (pericolic abscess) to IV (generalized fecal peritonitis) (►Table 2). Since then, with the introduction of CT to daily clinical practice, Wasvary et al, 32 in 1999, modified the original classification by adding non-complicated diverticulitis as stage 0, and subdivided stage I into two: stage Ia, with phlegmon or pericolic inflammation, and stage Ib, with pericolic or mesocolic abscess (►Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This retrospective study involved a cohort of 162 patients (age ≥18 years), treated at the Department of General Surgery, Tongren Hospital, Shanghai Jiao Tong University School of Medicine from December 2015 to December 2020. Acute RCD was defined according to previous studies, as the presence of colonic diverticular disease with localized colonic wall thickening and/or stranding of pericolonic fat [1,11,18]. A diagnosis of acute RCD was confirmed by abdominal ultrasonography (US), computed tomography (CT), colonoscopy, and further clinical assessments.…”
Section: Patients and Data Collectionmentioning
confidence: 99%
“…[8] Differentiation between acute uncomplicated and complicated diverticulitis seems debatable concerning the need for a routine colonoscopy. [9][10][11][12][13][14] Most industrialized countries have implemented screening programs for the early detection of CRC. Furthermore, it is established that screening colonoscopy (SC) is cost-effective and preventive.…”
Section: Introductionmentioning
confidence: 99%